COMPARISON OF BLOCK MAXIMA AND PEAK OVER THRESHOLD METHODS FOR EXTREME RAINFALL MODELING OF DKI JAKARTA - Akbar, Purnama (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Extreme rain has a form of tail that the right side of the distribution is longer; it is not suitable for model using normal distribution approach. One of the statistical methods developed related to the analysis of extreme events in which the shape of the data distribution sticks out to the right is the extreme value theory (EVT). Two approaches are often used in extreme value theory: the block maxima (BM) method and the peak over threshold (POT) method. This study aims to compare the alleged extreme rain in Jakarta Province in 1990-2019 with modifications to the maximum value retrieval in BM method and several approaches to selecting threshold values in POT method.  The two methods' comparison results show that the POT method is better at predicting extreme rainfall because it provides a value of root mean square error of prediction (RMSEP) value of 33.52 mm. This value is smaller than the RMSEP of the BM method, which is 47.92 mm.